Lexical means of expressing emotional state in english - Gordiienko, Yulia; Гордієнко, Юлія (Східноєвропейський національний університет імені Лесі Українки, 2014)
The article is about the differences between emotivity and expressiveness. The works of the linguists, who studied different means of expressing emotional state in English, especially lexical, grammatical, and syntactical ones, have been analyzed. It has been proved, that emotive component characterizes a word as the language unit. The basic principles of the process of lexical units categorization and the level of their use in the language system have been shown. The means of expressing positive and negative estimation of the emotional state are characterized. It is mentioned that negative lexical units with emotive meaning dominate over the positive ones in number, though they are used in speech more rarely. The attention is paid to the parts of speech, which are mainly used to express the emotional state – interjections, adjectives, nouns, adverbs, and verbs. Phraseological units with the emotive meanin are also classified. Different approaches to the classification of emotive lexicon are described. У статті розглянуто емотивність та її відмінності від експресивності. Проаналізовано роботи лінгвістів, які вивчали різноманітні способи вираження емоційного стану в англійській мові, а саме лексичні, граматичні, синтаксичні. Доведено, що емотивний компонент є ознакою слова як одиниці мови. Докладно проаналізовано основні принципи категоризації лексичних одиниць та ступінь використання цих засобів у мовній системі. Схарактеризовано способи вираження позитивної та негативної оцінки емоційного стану та доведено, що кількісно переважають негативні емотиви, хоч вони й застосовуються в мовленні рідше, ніж позитивні. Акцентовано увагу на частинах мови, які використовуються для опису емоційного стану – прикметниках, іменниках, прислівниках, вигуках. Окремо класифіковано фразеологічні одиниці, що мають емотивне значення. У статті описані різні підходи до класифікації емотивної лексики.
Лексичні засоби вираження емоційного стану в англійській мові
Keywords: emotivity; expressiveness; emotive component; emotive meaning; emotive lexicon; емотивність; експресивність; емотивний компонент; емотивне значення; емотивна лексика